MANGROVE LEAVES CRAFT: PEMANFAATANSAMPAH DAUN KERING MANGROVE SEBAGAI KERAJINAN MASYARAKAT PESISIR PANTAI TIMUR WONOREJO SURABAYA - Virrayani, Alifia Nurrizky; Subiyantoro, Dini Aiko; Nareswara, Shabrina; Biantoro, Ihsan; Ciputra, Ryan (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Most of people who live in coastal areas work as fisher who depend on their embankment, have started unproductive. Wonorejo Urban Village is an area in Surabaya East Coastal region which has the concept of ecotourism mangrove forest. Problems arise when the existence of people who manage this mangrove forest system misunderstood about the concept of ecotourism. Mangrove Leaves Craft programs answer the problems that exist in the Wonorejo Village, that educate the creativity of those community utilize mangrove leaves waste into economically valuable craft and thus become one of the ecological alternative livelihoods onWonorejo Village in Surabaya.